Religiusitas dan Stigma Perawat terhadap Orang dengan HIV (ODHIV) di RSUD Wates, Kulonprogo - Dwi Kartika Rukmi; Yuni Very Anto (MEDIA ILMU KESEHATAN, 2022)
Background: Previous research found that the stigma against HIV was higher in more religious nurses and often involved in religious activities. Objective: To see how the relationship between demographic characteristics and religiosity of nurses with stigma towards patients with HIV/AIDS.Methods: This research is an observational analytic study with a cross-sectional approach to 93 nurses at Wates Hospital. The research was held in May-September 2021 using a valid and reliable DUREL and Stigma questionnaire link distributed through Google Form after passing an ethical clearance. The data were processed using descriptive analysis and Spearman rho for correlation.Results: Nurses at Wates Hospital have a low stigma (52.7%), and high religiosity. There is a correlation between gender, religion, work experience in the HIV ward and the number of HIV patients who have been treated with religiosity. However, there is no correlation between demographic characteristics and religiosity with stigma among nurses.Conclusion: The stigma of nurses in Wates Hospital is in a low category and does not correlate with demographic characteristics and nurses' religiosity. The study results show that there are still some things related to the stigma that still need improvement to improve services for HIV patients by nurses at Wates Hospital.